Individualism vs. collectivism in a sharing economy context: A study on what determines Portuguese consumers’ participation - Cotrim, J.; Nunes, F. G. (6th International Workshop on the Sharing Economy: List of abstracts, 2019)
Consumers rely on warmth and competence, two fundamental dimensions that drive social judgments of people, to form perceptions of companies and, ultimately, make their market consumption decisions. In a Sharing Economy (SE) context, however, are there more profound and hidden motives for consumer behavior, namely the orientation–individualistic/idiocentric or collectivist/allocentric (Triandis & Gelfand, 1998) –of individuals of a given culture, for example? Meaning: does an individualistic/idiocentric orientation (in a “selfish” and “opportunistic” perspective without any kind of collectivist concerns that they are participating in something that is for the good of society and community as a whole) and/or a collectivist/allocentric orientation (in an “altruist” perspective, towards a collectivist/communal orientation) play a central role in determining consumers’ willingness to participate in sharing-based programs (SBP) of the SE? Furthermore, what drives such relationship? Meaning: what mediates such two variables (independent variable: individualism/collectivism; and dependent variable: willingness to participate)? In searching for an answer, this research conducted two studies: 1) Correlation –with the aim to find out whether these two variables are associated or related in some way, in other words, whether Individualism and/or Collectivism have a positive, a negative or no effect whatsoever on the willingness to participate in SBP of the SE; 2) Mediation analysis –with the aim to find out what explains (what mediates) the relationship between the two variables. Having Portuguese consumers as our targeted population, our tentative findings are expected to reveal that (i) individualism is the dominant dimension that plays a determinant role in influencing Portuguese consumer’s participation in the SE and (ii) such relationship is driven by the transformation expectations that such participation may in stil in their lives –at the level of emotions and experiential benefits. We present an innovative research, as, to the best of our knowledge, it is the first in investigating the relationship between individualistic/idiocentric or/and collectivist/allocentric orientation and consumers’ participation in SBP of the SE.